Eco-innovation and knowledge management: issues and organizational challenges to small and medium enterprises. Issue 2 (16th April 2019) - Cherifi, Ahmed; M'Bassègue, Patrick; Gardoni, Mickaël; Houssin, Rémy; Renaud, Jean
Abstract: The proposed methodology is based on a (global and multi-criteria) simplified environmental but thorough assessment. In this stage we do not directly give the solution to designers. It will therefore translate the results of evaluation design axes, but in general, the lines proposed are inconsistent or contradictory. Therefore, what we find is a compromise given to the solution. The challenge we are facing in an industrial reality is that one should not go for a compromise solution. TRIZ (Teorija Reshenija Izobretateliskih Zadatch) or the theory of solving inventive problems, in the field, will be reformulated and go through the contradiction matrix and then intervene with the principles of interpretation resolutions to give possible solutions. To assist small and medium enterprises (SMEs) in their product development, the objective of this paper is to propose a methodological approach named Ecatriz, that will allow us to achieve our eco-innovative goal. The applicability of this method is justified by the many contradictions in the choices in a study of the life cycle. As a starting point, a qualitative multi-criteria matrix will allow the prioritization of all impacts on the environment. A customized implementation of the inventive TRIZ ( Teorija Reshenija Izobretateliskih Zadatch, Russian acronym for theory of solving inventive problems) principles will help us choose eco-innovative solutions. To that end, we have created a new approach named Ecatriz (ecological approach TRIZ), based on a new contradiction matrix. It was tested in various contexts, such as the "24 h of Innovation" competition and eco-innovative patents.